2011
DOI: 10.21002/jaki.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Yang Mempengaruhi Kepuasan Kerja Auditor Dan Hubungannya Dengan Kinerja Dan Keinginan Berpindah Kerja Auditor

Abstract: This research aims to examine the factors that influence auditor's job satisfaction, the effects of job satisfaction on performance and turnover intentions, and how far the performances moderate the relationship between job satisfaction and turnover intention. The unit of analysis from this study is an auditor who works on a public accounting firm. Results showed that in small accounting firms, only consideration leadership style affects auditor's satisfaction, while in big accounting firms, leadership style a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 8 publications
(10 reference statements)
2
9
0
10
Order By: Relevance
“…If the leader is close to employees, respect to the employees opinion and to communicate openly would increase job satisfaction. Some previous research found the influence of leadership style and organizational commitment to job satisfaction and ultimately led to the turnover intention (Fitriany et al, 2011;Joo & Ready, 2012;Mehrad & Fallahi, 2014;Long et al, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Sun et al, 2016). Based on the basis of previous studies review and explanations described earlier, the fourt Hypothesis proposed in this study is: H4: Leadership Style has positive effect on Job Satisfaction.…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 66%
See 4 more Smart Citations
“…If the leader is close to employees, respect to the employees opinion and to communicate openly would increase job satisfaction. Some previous research found the influence of leadership style and organizational commitment to job satisfaction and ultimately led to the turnover intention (Fitriany et al, 2011;Joo & Ready, 2012;Mehrad & Fallahi, 2014;Long et al, 2014;Bateh & Heyliger, 2014;Siddiqui & Jamil, 2015;Sun et al, 2016). Based on the basis of previous studies review and explanations described earlier, the fourt Hypothesis proposed in this study is: H4: Leadership Style has positive effect on Job Satisfaction.…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 66%
“…Research conducted by Fitriany et al (2011) found that leadership style consideration has positive effect on job satisfaction. If the leader is close to employees, respect to the employees opinion and to communicate openly would increase job satisfaction.…”
Section: The Effect Of Organizational Commitment On Turnover Intentionmentioning
confidence: 99%
See 3 more Smart Citations